Levels of distress in breast cancer survivors approaching discharge from routine hospital follow‐up. Issue 8 (2nd December 2012) - Thompson, Joanne; Coleman, Rob; Colwell, Brigitte; Freeman, Jenny; Greenfield, Diana; Holmes, Karen; Mathers, Nigel; Reed, Malcolm
Abstract: Background: Hospital‐based breast cancer follow‐up provides reassurance to patients despite limited evidence for clinical efficacy. Although alternative models of hospital/community‐based follow‐up have yielded encouraging results, traditional hospital follow‐up continues to be offered to all patients. Survival rates continue to rise; consequently, more patients are likely to require support, as many have a limited understanding of the long‐term physical and emotional consequences of cancer and its treatment. We examine levels of psychological distress in breast cancer patients in follow‐up 2 years or more from diagnosis. Methods: This prospective study measured psychological distress levels using standardized measures [Hospital Anxiety and Depression Scale (HADS), Clinical Outcomes for Routine Evaluation (CORE) and Measure Yourself Medical Outcomes Profile (MYMOP)]. Between January and September 2008, 323 consecutive patients were approached in outpatient clinics. Ninety‐six patients declined to participate. Results: Two hundred twenty‐seven patients took home patient information sheets; 172 (75%) returned completed questionnaires to assess levels of distress (HADS, CORE). MYMOP provided self‐reported data on patient symptoms. Patients reported low levels of distress in hospital‐based follow‐up, which were comparable or better than general population norms, although there was a significant minority of patients reporting high scores ( n  = 27, 15.7%) on HADS or CORE. There was good agreement between these two measures. All sub‐scales of CORE (except risk) correlated well with HADS for anxiety/depression. No significant changes were detected in the standardized measures. MYMOP results showed that 23.8% of respondents reported both physical and emotional symptoms. Conclusions: Breast cancer survivors reported good psychological outcomes 2 years on from diagnosis. Screening for psychological/emotional distress is a vital part of follow‐up care, which should be incorporated into UK policy. Copyright © 2012 John Wiley & Sons, Ltd.